2015
DOI: 10.4103/0019-5154.147784
|View full text |Cite
|
Sign up to set email alerts
|

Acne vulgaris and quality of life among young adults in South India

Abstract: Acne vulgaris is a chronic condition affecting more than 85% of adolescents and young adults. It is one of the most common diseases affecting humanity and its impact on quality of life (QoL) is important. The impact of acne on QoL in Indian patients remains undocumented. The study was undertaken to detect the impact of acne vulgaris and related factors that may influence the QoL.Materials and Methods:This was a hospital-based, prospective, cross-sectional, prestructured, questionnaire-based study done on 140 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
90
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(114 citation statements)
references
References 33 publications
18
90
5
1
Order By: Relevance
“…Durai et al found that incidence of acne in adults is highest between 18-21years and 26-30 years. 17 As both acne and common warts occur in the young adults this was an expected finding.…”
mentioning
confidence: 80%
“…Durai et al found that incidence of acne in adults is highest between 18-21years and 26-30 years. 17 As both acne and common warts occur in the young adults this was an expected finding.…”
mentioning
confidence: 80%
“…13 Ejaz et al in regional study conducted in Rawalpindi found impaired quality of life in chronic skin conditions. 14 20 .…”
Section: Discussionmentioning
confidence: 99%
“…AV'li hastalarda yaşam kalitesini değerlendirmek amacı ile farklı ölçekleri kullanan birçok çalışma yapılmıştır (6)(7)(8). Yapılan bir çalışmada akne grubu hastalıklar özel muayenehaneye en sık (%15,2) başvuru nedeni iken, kamu hastanesine ikinci sıklıkta (%15,8) başvuru nedenini oluşturmuştur (9).…”
Section: Introductionunclassified